External factors involved in the regulation of synthesis of an extracellular proteinase in Bacillus megaterium: effect of temperature - Vortuba, Jaroslav; Pazlarova, Jarmila; Dvorakova, Milada; Vachova, Libuse; Strnadova, Marie; Kucerova, Helena; Vinter, Vladimir; Zourabian, Rimma; Chaloupka, Jiri (Applied microbiology and biotechnology, 1991)
We studied the effect of temperature on the production of an extracellular neutral metalloproteinase of Bacillus megaterium in a laboratory fermentor under constant aeration and pH. The optimal temperature for growth (35-38° C) was higher than that for the synthesis of proteinase during exponential growth (below 31° C). The critical biomass concentration at which the exponential growth terminated decreased with increase in cultivation temperature. The specific rate of proteinase synthesis decreased when the critical biomass concentration was achieved. The observed decrease in proteinase synthesis was related to the cultivation temperature. The temperature also influenced the level of mRNA coding for proteinase. We formulated a mathematical model of cultivation describing the dependence of growth and proteinase synthesis on dissolved oxygen and temperature. The parameters of the model were identified for temperature intervals from 21 to 41° C using a computer. The optimum temperature for the enzyme production was 21° C. The productivity (enzyme activity/time) was maximal at 24-28° C. When optimizing the temperature profile of cultivation, we designed a suboptimal solution represented by a linear temperature profile. We have found that under conditions of continuous decrease in temperature, the maximal production of the proteinase was achieved at a broad range of temperature (26-34° C) when the rate of temperature decrease was 0.2-0.8° C/h. The initial optimal temperature for the enzyme productivity was in the range of 32-34° C. The optimum temperature decrease was 0.8° C/h.